A Brief Review on Citrullus colocynthis- Bitter Apple - Alka Rani; Anju Goyal; Sandeep Arora (Archives of Current Research International, 2017)
Present review article reveals the importance of species Citrullus colocynthis, distributed in India and other parts of the world; this extensive research information on this species is highly significant for future researchers worldwide. In this article morphological and biological activity, inputs have been extensively recorded and discussed. As a part of our investigation on morphological and biological aspects of important medicinal plants from India, the aim of this pioneer attempt is to provide precise, truthful and detailed information of C. colocynthis.